Attention Deficit Democracy : The Paradox of Civic Engagement - Berger, Ben, 1968- (Book collections on Project MUSE., 2011)
Handwringing about political apathy is as old as democracy itself. As early as 425 BC, the playwright Aristophanes ridiculed his fellow Athenians for gossiping in the market instead of voting. In more recent decades, calls for greater civic engagement as a democratic cure-all have met with widespread agreement. But how realistic--or helpful--is it to expect citizens to devote more attention and energy to politics? In Attention Deficit Democracy, Ben Berger provides a surprising new perspective on the problem of civic engagement, challenging idealists who aspire to revolutionize democracies and their citizens, but also taking issue with cynics who think that citizens cannot, and need not, do better.